Adhoc Setup of an Online Mental Health Self-Help Program During the COVID-19 Pandemic: Description of the Development and Implementation Processes and Analysis of Its Users’ and Usage Profiles - Galffy, Matyas; Bichler, Carina; Mohr, Thomas; Egeter, Jonas; Neu, Leonie; Oberhammer, Maria; Högl, Birgit; Deisenhammer, Eberhard A.; Sperner-Unterweger, Barbara; Hüfner, Katharina (Frontiers in Psychology, 2022)
Background: The COVID-19 pandemic hit Austria in March 2020. During these times outpatient psychiatric therapies had to be reduced considerably. People with mental disorders as with newly emerging mental health issues found themselves with very limited treatment options. Within only a few days our hospital set up an online mental health self-help program which went online in its first version on the first day of the lockdown in Austria. The process of this development and implementation process alongside with the user and usage data for the program are presented here. Methods: A small core team initiated the development of the program on a low-budget basis and using mostly freely available digital resources. The program had to be free of costs for its users and easy to navigate. Each self-help module contains a text description of the topic, a self-rating questionnaire and several psychoeducational 2-5 minute videos. These videos explain e.g. interactions of mental stress and the immune system or the vicious circle of anxiety. Results: We illustrate the implementation of this program following the replicating effective program (REP) model. We provide a detailed description of the implementation process starting from a simple website to a smartphone-based application with registered user area and instantaneous reporting of self-rating questionnaire results to users. The described process could be used as a model for the setup of similar programs in a very short time. As an indicator of acceptance, we report 46,100 unique video views and 3,937 completed questionnaires in the first year of use. The most accessed videos were those on anxiety, relaxation and resilience. Analysis of the sociodemographic user data indicate that they were mostly young (<45 years; 59.7%), females (77.5%) and previously mentally healthy individuals (74.5%). An example of the collected psychometric questionnaire data over time is given. Conclusion: We show that it is possible to set up an online mental health self-help program ad hoc and without extensive prior planning, which enabled us to dynamically respond to a new situation. We are now planning to supplement and expand traditional treatment settings also outside the COVID-19 pandemic.